An IQ domain mediates the interaction with calmodulin in a plant cyclic nucleotide-gated channel. - Fischer, Cornelia; Kugler, Annette; Hoth, Stefan; Dietrich, Petra (Plant & cell physiology, 2013)
Cyclic nucleotide-gated channels (CNGCs) form non-selective cation entry pathways regulated by calmodulin (CaM), a universal Ca(2+) sensor in eukaryotes. Although CaM binding has been shown to be important for Ca(2+)-dependent feedback regulation of CNGC activity, the CaM-binding properties of these channels have been investigated in a few cases only. We show that CNGC20 from Arabidopsis thaliana binds CaM in a Ca(2+)-dependent manner and interacts with all AtCaM isoforms but not with the CaM-like proteins CML8 and CML9. CaM interaction with the full-length channel was demonstrated in planta, using bimolecular fluorescence complementation. This interaction occurred at the plasma membrane, in accordance with our localization data of green fluorescent protein (GFP)-fused CNGC20 proteins. The CaM-binding site was mapped to an isoleucine glutamine (IQ) motif, which has not been characterized in plant CNGCs so far. Our results show that compared with the overlapping binding sites for cyclic nucleotides and CaM in CNGCs studied so far, they are sequentially organized in CNGC20. The presence of two alternative CaM-binding modes indicates that ligand regulation of plant CNGCs is more complex than previously expected. Since the IQ domain is conserved among plant CNGCs, this domain adds to the variability of Ca(2+)-dependent channel control mechanisms underlining the functional diversity within this multigene family.